Exploratory Survey at the Mexican Marketplace on Pork Muscles Characteristics From U.S.A. and Mexico - Méndez Medina, Rubén Danilo; Ponce Alquicira, Edith; Rubio Lozano, María Salud; Ryan, Suzanne; Huerta Leidenz, Nelson (Revista Científica de la Facultad de Ciencias Veterinarias)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> <!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Trends in variation of physical, chemical and sensory traits due to country of origin (COO) were evaluated for samples from United States of America (U.S.A.) and Mexico of three pork muscles, Rectus femoris (RF, n = 20 from each COO), Vastus medialis (VM, n = 20 from each COO), and Longissimus dorsi (LD, n = 10 from each COO) in two separate, small-scale, exploratory surveys conducted at Mexico City. Compositional, physical and chemical properties and consumer acceptability traits of these Mexican and U.S.A. pork samples were quite similar, though Mexican pork samples generally were more variable. LD samples from U.S.A. had greater (P<0.05) water-holding and emulsifying capacities whereas both RF and LD from U.S.A. required lower shear force (P<0.05) compared to Mexican counterparts. Ratings from consumers did not indicate preference for pork from any of the countries. Because of the limited number of observations for the samples surveyed these results are preliminary and may not adequately characterize the populations of each country, but they did reveal important trends for selected traits of Mexican and U.S.A. pork currently available at the local market. Â Â